2019
DOI: 10.2174/1381612825666191107162921
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotypes of Severe Cutaneous Drug Hypersensitivity Reactions

Abstract: Drug hypersensitivity reactions are clinically heterogenous ranging from mild to severe. Most drug hypersensitivity reactions are accompanied by cutaneous manifestations. Fever, mucous membrane involvement, large blisters, facial oedema, pustulosis and visceral involvement are clinical features that lead to suspicion of severe adverse drug reactions. Severe cutaneous adverse drug reactions (SCARs) include Stevens-Johnson syndrome, toxic epidermal necrolysis, drug rash eosinophilia and systemic symptoms, acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 133 publications
0
12
0
1
Order By: Relevance
“…1,2 Cutaneous adverse drug reactions (CADRs) are the most frequent adverse events resulting from medication use. 3 CADRs encompass all adverse events related to drug eruption, regardless of aetiology. 4 Studies have shown that CADRs comprise 10%-20% of reported ADRs and have an overall incidence rate of 2%-3% in hospitalized patients and approximately 2%-6% among all patients treated, with incidence of severe CADRs (SCADRs) ranging from 0.33% to 3%.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Cutaneous adverse drug reactions (CADRs) are the most frequent adverse events resulting from medication use. 3 CADRs encompass all adverse events related to drug eruption, regardless of aetiology. 4 Studies have shown that CADRs comprise 10%-20% of reported ADRs and have an overall incidence rate of 2%-3% in hospitalized patients and approximately 2%-6% among all patients treated, with incidence of severe CADRs (SCADRs) ranging from 0.33% to 3%.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…1. Violation of medical record writing and management system 46 (18) Medical records and/or prescriptions were not available for the time of the patient's visit 7 (3) Medical record writing does not meet the requirements of 'basic specification for medical record writing' 39 (16) 2. Inadequate informed consent 51 (20) Insufficient information on side effects, adverse reactions, precautions and risks of drugs.…”
Section: What Is Ne W and Con Clus I Onmentioning
confidence: 99%
“…(%) 58 (78.4) Mean eosinophil count, × 10 9 /L 0.19[0.22] Eosinophilia-no. (%) 56 (75.7) Median AST, U/L [IQR] 18.0 [12] Elevated AST*–no. (%) 7 (9.5) Median ALT, U/L [IQR] 22.0[24] Elevated ALT*–no.…”
Section: Resultsmentioning
confidence: 99%
“…The prolonged AGEP following the use of hydroxychloroquine was formerly reported in the literature as case reports [12] , [13] , [14] , [15] . However, to the best of our knowledge, no study has yet to compare the improvement time of hydroxychloroquine-induced AGEP with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The sequelae of events that resulted in a diagnosis of antibiotic allergy, with all children in our study, began with a red, raised rash, but rarely any further investigations. Whereas antibiotic allergy may present with a cutaneous manifestation and necessitate withdrawal, 18 infants and children develop rash for a multitude of other reasons, including rarely related Immunoglobulin E-mediated allergic conditions, 10 as well as viruses 19 and infections. 20 Macular/ popular rashes in childhood are often harmless and are commonly attributed to viral infections.…”
Section: Discussionmentioning
confidence: 99%